A precious-metal-free Fe-intercalated carbon nitride porous-network with enhanced activity for the oxygen reduction reaction and methanol-tolerant oxygen reduction reaction. Issue 10 (11th August 2020) - Yousaf, Ammar Bin; Monnier, John R.; Weidner, John W.; Hassan, Mohammad K.; Zaidi, Syed Javaid; Kasak, Peter
Abstract : The economical cost of the catalyst material has remained a challenging task in traditional fuel cells (FCs) and in direct methanol fuel cells (DMFCs). Abstract : The economical cost of the catalyst material has remained a challenging task in traditional fuel cells (FCs) and in direct methanol fuel cells (DMFCs). However, replacement of noble metals with precious metal-free materials as catalysts has raised issues regarding their performance. Among them, cathodic catalysts have unresolved issues regarding working conditions, where they must be resistant to the effect of fuel crossover from the anode to maintain stable electrochemical behavior. We have focused on multiple factors to address these challenges and contribute to the field of DMFC electrocatalysis and have successfully lowered the high cost of the usual Pt catalyst by developing a non-precious metal-based Fe–N–C material as the cathode catalyst. Organic polymers in combination with C and N-rich sources of organic acids constitute the highly active Fe–N–C precursor by in situ intercalation of Fe, facilitated by pyrolysis. The C and N-rich additives help generate abundant Fe–N x and N–C active sites for enhanced oxygen reduction reaction (ORR) under acidic and alkaline conditions and show a negligible decrease in activity after 2000 scan cycles. Moreover, the active sites for ORR electrocatalysis showed excellent stability for methanol tolerance, thereby resulting in enhanced and durable performance for DMFCs as well as for PEMFC systems.